Perbandingan Sistem Jaminan Sosial Antara Indonesia Dan Malaysia Dalam Rangka Pemenuhan Hak Kesehatan Di Indonesia - Hayanti, Vivi; Dompak, Timbul (Prosiding, 2024)
Everyone on this planet is worried about their health. It is explained in paragraph 25 (1) of the 1948 United Nations Declaration on the History of Humanity, which states that "Everyone has a responsibility to maintain the standard of life that can be taught them to follow." In accordance with the legal system of the State, as well as the rights of foreigners, women's rights, health and welfare care, and social services are protected from the use of force during pregnancy, childbirth, breastfeeding, being a widow or widow, reaching adulthood, or other incidents that may lead to a decrease in livelihoods.Having considered this, every nation has a duty to protect the health of its citizens. Each country has a different system to protect its people's health. There are two types of insurance systems in the world: primary insurance with government subsidy (Traditional Sickness Insurance), government concept of providing national health